Pediatric Echinococcosis: diagnosis, urgent surgical intervention, and treatment – case report - Memeti, Shaban; Sulejmani, Haris; Risteski, Toni; Cokleska Shuntov, Natalija; Racaj, Anila; Ljumani Bakiu, Njomza; Kamilovski, Marijan; Gjuric, Sanja; Selmani, Rexhep; Rushiti, Qemal (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2024)
Echinococcus tapeworms cause human echinococcosis, which causes hydatid cysts, most commonly in the liver and lungs but also in other organs. Delays in symptom onset can lead to diagnostic issues, especially in children. Pediatric cases are rare and often lead to unintentional diagnoses. Living in a rural area increases risk. Imaging and serological testing are essential for diagnosis. This case is rare since it involves pediatric echinococcosis. Children rarely get echinococcosis, and symptoms are often vague; thus, diagnosis is mainly by accident. Case report: A 10-year-old female child developed symptoms and signs such as tachycardia, fever, and facial urticaria. On the first clinical examination, classic signs of an acute abdomen were present, indicating a possible abdominal emergency. Laboratory results showed significantly high levels of inflammatory markers, including CRP and WBC, indicating an active inflammatory process, most likely caused by infection or tissue injury. Imaging examinations, particularly a contrast CT scan of the abdomen, revealed two burst liver cysts in the peritoneal cavity, confirming the diagnosis of echinococcal cysts in the liver. We undertook an urgent surgical intervention to address the burst cysts and avert potential complications like peritonitis or sepsis. Post-operative treatment included constant monitoring of the patient's condition, antibiotic and antihelminthic medication to control infection, pain management, and supportive measures to help with recovery. Echinococcosis in children manifests as nonspecific symptoms, which often leads to a rare suspicion and coincidental diagnosis. Echinococcosis is often considered a possible cause of stomach discomfort. The standard treatment for echinococcosis usually involves a combination of antiparasitic medication and surgical removal of the cyst.
Keywords: ecchinococcosis; children; imaging methods; treatment; surgery